PENGUATAN KETERAMPILAN PEMASARAN SISWAMELALUI PEMAHAMAN MANAJEMEN BAURAN PEMASARANDI SMK MULIA BUANA PARUNG PANJANG BOGOR - San Ridwan Maulana; Syabrina Fitriyani; Budhi Prabowo (LAP4B, 2026)
Marketing skills are fundamental competencies that must be mastered by business major vocational high school students to face increasingly competitive workplace challenges. This Community Service Program aims to strengthen the marketing skills of SMK Mulia Buana Parung Panjang students through comprehensive understanding of marketing mix management that is applicable and in accordance with digital era developments. The activity was conducted on March 7-9, 2026 using interactive learning methods that combine lectures, practical workshops, real product marketing case studies, and marketing strategy formulation simulations. Program participants were 46 students from grades XI and XII of the Business and Marketing expertise program selected based on learning motivation and career plans in marketing field. Evaluation results showed a significant increase in marketing mix understanding with average pre-test scores of 64.3 increasing to 85.6 on post-test, indicating a 33% improvement in material mastery. Practical skills assessment through marketing plan projects showed 88% of participants were able to develop comprehensive and creative marketing mix strategies for their chosen products. Satisfaction survey showed 92% of participants rated the program as very beneficial and 87% felt more prepared for careers in marketing or starting their own business. This program proves that structured and contextual marketing mix training can effectively equip vocational students with solid marketing competencies relevant to modern industry needs.